Major savings and production efficiencies with wear-resistant ceramics - P. A. Verhey (Canadian Institute of Mining, Metallurgy and Petroleum, 1981)
"This paper describes a series of wear-resistant ceramic materials which have been successfully used in the mineral processing industry in Canada. Applications include use with metallic ores, coal, potash and asbestos, and in other processes where wear degradation is of major concern. The paper will also deal with considerations involving the selection of the different ceramic materials available. It will cover the installation of ceramic materials on support structures under varying process ' conditions, as well as the other physical and chemical factors which have to be taken into account.IntroductionIn the mineral processing industry, large volumes of ores tailings and other materials are handled. The abrasive nature of most of these materials results in extensive wear to both handling and processing equipment.Wear ratios versus cost, production losses due to down time and wear-resistant material suitability for a given application all demand particular attention when viewed against the need for increased efficiencies in existing processes. As a consequence, a very active continuous search for materials with improved wear resistance has been carried out for many years.In this search, starting about 20 years ago, dense ceramic materials were tested and evaluated in certain applications, notably in the iron ore and asbestos operations in Eastern Canada. As a result of substantially better performance both in continuous extended life and ultimate economics realized , wear-resistant ceramic applications developed progressively in many other processing applications, replacing traditionally used materials.In the vast majority of wear-resistant ceramic applications, considerable extended life over previously used materials was established. This invariably was not just a fractional increase but, in most cases , in factors of double, triple and often all the way up to 18 and 20 times the life of alternative materials used previously. In certain applications, extended life could not be measured and appears to be indefinite.Obviously, as a result of such experiences, the progressively wider use of wear-resistant ceramic materials is now an established trend."